Distribution Chain and Potential of Gonggong as a Culinary Tourism Destination in Bintan Island - Hary Jocom (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2022)
This study aims to identify the Gonggong (dog conch) supply chain in Bintan Island and identify its potential to become a culinary tourism destination besides the well-known natural and cultural tourist destinations in Bintan Island. This is motivated by the existence of gonggong as endemic animals that only exist in the Riau Islands, especially in Bintan and Bangka Belitung Islands so that gonggong is known as a typical food of Bintan Island. However, this typical of Bintan Island is not yet nationally known like special foods of other regions. This study was conducted in Bintan Island using a descriptive-qualitative method to describe the supply chain and the potential of gonggong as a special food for culinary destination. Data was collected through in-depth and structured interviews and observations. The results of this study indicate that in terms of quantity, gonggong is available throughout the year with a tendency of abundant availability, and as a result, it has the potential of culinary destination for Bintan Island. In order for the gonggong culinary to be attractive to tourists, it needs packaging in a series of tourist travel attractions emphasizing foods and integrating it with cultural values of the local communities and with the rich natural phenomena of Bintan Island. Digital marketing strategies can be used for the purpose above through various social media or e-commerce platforms that are packaged in an attractive manner to build tourists’ perception that Gonggong is the typical culinary destination of Bintan Island that is worthy of visit.